The military budget and you - Baker, Glenn (Washington : Center for Defense Information, 1997)
American taxpayers paid $13.4 trillion to fight the Cold War. Annual spending on the military averaged $304 billion per year between 1948 and 1995. For comparison, the entire 45,000-mile interstate highway system cost $150 billion over its 40-year development
Executive producer, Gener R. LA Rocque
Narrator: Margeret Knudson
Keywords: Class distinction; Military art and science; Economics